Disaster preparedness and mitigation in informal settlements: community and municipal roles in the case of Stjwetla in Alexandra, Johannesburg - Ngove, Pheni; Pheni, Ngove (My University, 2020)
This study looked into the extent of coordination between municipalities and communities in preparing for and mitigating disasters. Using qualitative methods in key informant interviews, it compiled a case study of Stjwetla informal settlement in Alexandra, Johannesburg. The study was motivated by the fact that despite South Africa having been one of the first countries in Africa to adopt legislation on Disaster Risk Management (DRM), and despite the legislation having been praised as significant and progressive, the response to disasters on the ground has been characterised by reactionary rather that proactive measures. As such, the study identified the gap between what the DRM legislation sought to achieve and what transpires on the ground. The findings of this study suggest that collaboration between communities, municipal officials and non-governmental organisation plays a huge role in disaster and risk management in Informal settlements
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Masters of Built Environment in the field of Housing, 2020